(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Objective: To evaluate the efficacy of 60 mg diluted 2% intravenous (IV) lignocaine (60 mg in 4cc) by intermittent venous occlusion (occlusion time 15 sec/cc, 5 sec gap, 4 occlusion) vs without venous occlusion to prevent pain of propofol injection. Background: Propofol is one of the most common anesthetic agents used because of its unique pharmacological properties. But, pain of Propofol injection is one of the most common and day to day problem faced by anesthetists. Even though various studies have been used to decreases pain of propofol injection, it has still remained as an unsolved problem. Previous studies with venous occlusion have been done which have not shown much relief. The cause may be due to inadequate time for lignocaine to act on the endothelium. This study highlights different methods of giving 60mg diluted IV 2% lignocaine (preservative free) to prevent the pain of propofol injection. Method: 40 Patients with age range (18-65) years and classified ASA 1 and ASA 2 undergoing general anaesthesia for elective surgery were included in this study. Patients were randomized into 2 groups; GROUP A (n=20) received 60mg diluted IV 2% lignocaine (preservative free) by intermittent venous occlusion; i.e., 4cc (3cc of IV 2% lignocaine + 1 cc of normal saline) (occlusion time 15 seconds/cc; 5 seconds gap; 4 occlusions) and GROUP B (n=20) received 60 mg diluted IV 2% lignocaine (preservative free) without venous occlusion slowly over 30 seconds. The primary objective was to compare the prevention of pain of propofol injection by verbal rating score. The secondary objective was to study the change in pressor response on laryngoscopy. Results: Patients receiving 60 mg diluted IV2% lignocaine (preservative free) by intermittent venous occlusion experienced significantly less pain after injecting propofol compared to patients receiving 60 mg diluted IV 2% lignocaine (preservative free) without venous occlusion. There was a significant difference in pressor response seen to laryngoscopy also. Group A patients had less pressor response seen in comparison to Group B. Conclusion: Reduction of pain due to propofol injection with our method of intermittent venous occlusion i.e., occlusion time 15 seconds/cc; 5 seconds gap; 4 occlusions, shows better results as sufficient time is given for IV lignocaine to act on the endothelium. Pain of propofol injection can be reduced by just putting in some extra time and attention while giving a lignocaine before the drug.